The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/app7040377
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Behaviors of Nitrogen Dioxide Absorption in Sulfite Solution

Abstract: Abstract:The simultaneous removal of nitrogen oxides (NO x ) and sulfur dioxide (SO 2 ) by absorption is considered to be one of the most promising technologies for flue gas treatment, and sulfite is the main component of the absorption solution. To understand the chemical behaviors of the NO 2 absorption in sulfite solution, the absorption time dependences of concentrations of nitrogen and sulfur compositions in both gas phase and liquid phases were investigated by flue gas analyzer, Ion chromatography (IC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In many experimental studies on air pollution, NO 2 is often used as a catalyst for producing sulfates from bisulfite ion (HSO 3 – ) or sulfite ion (SO 3 2– ) in the lead chamber process (for producing sulfuric acid in large quantities). In these studies, the chemical mechanism responsible for the formation of sulfate through active nitrogen was mainly due to the direct contact between NO 2 and HSO 3 – /SO 3 2– , as independently proposed by Lee et al, Clifton et al, and Littlejohn et al Specifically, Spindler et al proposed that at pH 4.5, the first step in the electron-transfer reaction is HSO 3 – (aq) + NO 2 (aq) → SO 3 – (aq) + H + (aq) + NO 2 – (aq), which proceeds through a [HSO 3 –NO 2 ] − intermediate, with the N-atom of NO 2 being directly bonded to one O-atom of HSO 3 – ; at pH 10.0, the initial step in the aqueous reaction of dissolved NO 2 with SO 3 2– is NO 2 (aq) + SO 3 2– (aq) → [SO 3 –NO 2 ] 2– (aq) . These experimental studies on the aqueous conversion of HSO 3 – /SO 3 2– to sulfate via dissolved NO 2 were performed by flowing gaseous NO 2 through bulk solutions of NaHSO 3 or Na 2 SO 3 …”
Section: Introductionmentioning
confidence: 92%
“…In many experimental studies on air pollution, NO 2 is often used as a catalyst for producing sulfates from bisulfite ion (HSO 3 – ) or sulfite ion (SO 3 2– ) in the lead chamber process (for producing sulfuric acid in large quantities). In these studies, the chemical mechanism responsible for the formation of sulfate through active nitrogen was mainly due to the direct contact between NO 2 and HSO 3 – /SO 3 2– , as independently proposed by Lee et al, Clifton et al, and Littlejohn et al Specifically, Spindler et al proposed that at pH 4.5, the first step in the electron-transfer reaction is HSO 3 – (aq) + NO 2 (aq) → SO 3 – (aq) + H + (aq) + NO 2 – (aq), which proceeds through a [HSO 3 –NO 2 ] − intermediate, with the N-atom of NO 2 being directly bonded to one O-atom of HSO 3 – ; at pH 10.0, the initial step in the aqueous reaction of dissolved NO 2 with SO 3 2– is NO 2 (aq) + SO 3 2– (aq) → [SO 3 –NO 2 ] 2– (aq) . These experimental studies on the aqueous conversion of HSO 3 – /SO 3 2– to sulfate via dissolved NO 2 were performed by flowing gaseous NO 2 through bulk solutions of NaHSO 3 or Na 2 SO 3 …”
Section: Introductionmentioning
confidence: 92%
“…The initial NO 2 and O 3 levels after the plasma discharge process were fixed at 480 ppm and 330 ppm, respectively. It can be concluded that NO 2 and O 3 were completely absorbed by Na 2 SO 3 in the initial 40 min, and the promotion of Na 2 SO 3 absorption concentration and the increase of pH value will prolong NO 2 and O 3 removal effectiveness [ 48 ]. The post sodium-based alkali solution absorption is an effective application of the NTP technique in industrial flue gas treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The interactions between nitrogen and sulfur are highly dependent on the pH level due to the dissociative reaction . At pH values ≥7, SO 3 2– is the dominant form, and reaction creates a potential route for NO 2 hydrolysis Reaction has been studied experimentally, and it has a significantly higher reaction rate than reaction . This interaction between S­(IV) and NO 2 (aq) makes the simultaneous absorption of NO 2 and SO 2 an effective process under alkaline conditions.…”
Section: Chemistrymentioning
confidence: 99%